The Right to Hospitality in International Economic Law: Domestic Investment Laws and the Right to Invest - Georgios Dimitropoulos (19342807) (2023)
Under the Liberal International Order (LIO) of the post-WWII years, foreign investment protection was meant to be granted by international law and institutions. But current economic de-globalization is giving way to institutional and legal de-globalization. Domestic laws relating to foreign investment, especially in the form of Domestic Investment Laws, are taking over International Investment Agreements as the standard means of regulating cross-border trade and investment flows. The article compares substantive and procedural standards of investor protection in international and domestic investment law, as well as old and new Domestic Investment Laws, with a focus on non-discrimination and dispute settlement. The move to domestic law in IEL does not always signify a trend for most states to isolate themselves from the international economy. Rather, it is often an effort to achieve similar ends as those of the LIO but using different means. The article discusses an alternative political economy framework for an international (economic) law of ends, the cornerstone of which is the right to hospitality. Other Information Published in: World Trade Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/s1474745622000416